PEMBELAJARAN STATISTIKA DENGAN PENDEKATAN SAINTIFIK BERBASIS PENDIDIKAN POLITIK - Rina Nur Afifah (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
One learning approach that is able to encourage students to learn actively is a scientific approach. a scientific approach is a learning approach whose activities include observing, asking questions, gathering information / trying, reasoning / associating and communicating.Scientific approach based on political education is a learning approach offered by researchers that is an approach by following the steps of a scientific approach by linking teaching material with political issues in the environment both the school environment and political problems in society. By applying this learning approach students are expected to more easily understand teaching material because it is directly related to its application in daily life so that learning becomes more meaningful and with political education based is expected to be one of the teacher's efforts in socializing politics among students.This research will discuss about efforts to improve students' statistical understanding with a scientific approach based on political education in the school environment.